SmBaCo2O5-d as high efficient oxygen electrode of solid oxide electrolysis cells - Wei, B.; Chen, K.; Zhao, L.; Ai, N.; Lü, Z.; Jiang, San Ping (Electrochemical Society Inc., 2013)
Oxygen electrode is a key component for solid oxide electrolysis cells (SOECs). Double perovksite oxide SmBaCo2O5-d (SBCO) exhibits high electrical conductivity and fast oxygen transport properties, herein we proposed SBCO as a novel high efficient SOEC oxygen electrode based on Ce0.9Gd0.1O1.9 (GDC) electrolyte. Preliminary study showed that an area specific resistance of 0.024 ?cm2 was achieved under OCV condition at 900°C and a stable operation of 20 h was obtained at an anodic polarization current density of 200 mA.cm-2. © The Electrochemical Society.